(untitled) (Journal of the College of Education for Women, 2019)
Dying poetry ,last felt the man to say apriorior improvisation during entry in to thecontext of the death while going through it, or distracted by the death , before the soul wentout the duration of a brief may not exceed the minutes , with out pious or pen or vain , mayhave been exercised in his daily life, compelled or for the benefit.The discussion dealt with the meaning of dying, then presented its article with threetopics;First; What was said in accepting the death.Second; what was said in the reguest fo death.Third; what was said to ignore the death.This lesson as well as poetry style andcream and the imeanings and ideas and nages andrhetorical rhythm. To achieve this, adopted solid sources and references of the value of literature,translation, history, ianguage, totaling fivty five asource and areference.